The Motivation of Malays to Enter the Syattariyah Order: A Study of the Teachings of Tuan Sheikh Silau Laut - Syukri Syukri; Sulaiman Muhammad Amir; Safria Andy (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The Syattariyah Order is one of the orders that developed in the Indonesian archipelago, including among the Malay community. One of the central figures in the spread of this order is Tuan Syekh Silau Laut, who has had a significant influence on the spiritual formation of the Malay community. This study aims to analyze the motivations of Malays in entering the Syattariyah Order by referring to the teachings of Tuan Syekh Silau Laut. The research method used is qualitative with a historical and phenomenological approach. Data were obtained through literature study and interviews with followers of the order. The results show that the main motivations of Malays in joining the Syattariyah Order include the desire to get closer to God, seek inner peace, and receive spiritual guidance from a murshid who is considered to have blessings. The teachings of Tuan Syekh Silau Laut, which emphasize aspects of practical Sufism and moral development, are a key factor in attracting community interest. In conclusion, the Syattariyah Order plays a role not only as a spiritual system, but also as a means of forming the religious and social identity of the Malay community.